The Impact of Various Priming Treatments on Rato Basmati Rice Variety - Dhami, Arati; Limbu, Anka Kumari; Karki, Mamata; Kshetri, Karishma; Subedi, Kabita; Gaire, Achyut (International Journal of Applied Sciences and Biotechnology, 2024)
An important crop, used as stable food worldwide is rice. The germination stage is crucial for rice crop and is mainly affected by drought stress. A laboratory experiment was conducted in GAASC laboratory, Gokuleshwor, Baitadi to study the impact of various priming treatments on Rato basmati rice variety. The experiment was done in a completely randomized design using 9 treatments replicated thrice. The treatments were Hydro priming 24hrs, Hydro priming 12hrs, Gibberellin 5mg/liter, Gibberellin 10mg/liter, Gibberellin 15mg/liter, NaNO3 0.5%, NaNO₃ 5%, NaNO₃ 15%, and control where seeds were washed three times followed by 5 hours drying at room temperature. For 10 days, each Petri plate was observed every 12 hours. The priming treatment with Gibberellin 10mg/L showed the most promising results for germination percentage (100%) within 120 hours, Germination index (11.06) and germination energy (0.97), while Gibberellin 15 mg/L showed higher vigor index (1522), plumule length (40.02 cm), radicle length (15.73 cm). However, the germination energy (0.93) was found similar in Gibberellin 15 mg/L and 24hrs hydropriming. Regarding Plumule to radicle length ratio, highest result was obtained from 24hrs hydropriming (0.55 cm). Thus, this study suggests that using Gibberellin of both 10 and 15 mg/L for priming in rato basmati variety of rice showed the best results compared to other treatments.Int. J. Appl. Sci. Biotechnol. Vol 12(4): 187-193.